2008
DOI: 10.1029/2007tc002141
|View full text |Cite
|
Sign up to set email alerts
|

Geologic implications of new zircon U‐Pb ages from the White Mountain Peak Metavolcanic Complex, eastern California

Abstract: [1] The NNW-trending White-Inyo Range includes intrusive and volcanic rocks on the eastern flank of the Sierran volcano-plutonic arc. The NE-striking, steeply SE-dipping Barcroft reverse fault separates folded, metamorphosed Mesozoic White Mountain Peak mafic and felsic volcanic flows, volcanogenic sedimentary rocks, and minor hypabyssal plugs on the north from folded, well-bedded Neoproterozoic-Cambrian marble and siliciclastic strata on the south. The 163 ± 2 Ma Barcroft Granodiorite rose along this fault, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…150-135 Ma (Crowder and Sheridan, 1972;Dunne et al, 1978Dunne et al, , 1998Hanson et al, 1987). Employing secondary ion mass spectrometry (SIMS) techniques, Scherer et al (2008) demonstrated that in the White Mountain Peak area, volcanism occurred during the interval ca. 155-110 Ma.…”
Section: Arc Volcanic Rocksmentioning
confidence: 99%
See 1 more Smart Citation
“…150-135 Ma (Crowder and Sheridan, 1972;Dunne et al, 1978Dunne et al, , 1998Hanson et al, 1987). Employing secondary ion mass spectrometry (SIMS) techniques, Scherer et al (2008) demonstrated that in the White Mountain Peak area, volcanism occurred during the interval ca. 155-110 Ma.…”
Section: Arc Volcanic Rocksmentioning
confidence: 99%
“…170 Ma, and that the so-called mag-matic gap at ca. 140-125 Ma in the arc (Stern et al, 1981;Chen and Moore, 1982;Hacker et al, 1995;Wooden et al, 1999) might have been due to an increased ratio of volcanism to plutonism-combined with subsequent preferen tial erosion of the extrusive units-rather than to a period of oblique-convergence-induced igneous quiescence (Glazner, 1991;Bateman, 1992;Scherer et al, 2008). Calc-alkaline volcanism thus seems to have characterized the active continental margin arc over the entire interval from ca.…”
Section: Arc Volcanic Rocksmentioning
confidence: 99%